Improving the Organizational Attractiveness in the Job Choice by Communicating CSR Practices - Mufid Salim (Ikatan Sarjana Komunikasi Indonesia, 2018)
This study is purposed to examine the relationship between providing information of CSR practices with organizational attractiveness in the job choice among prospective applicants. Drawing from signaling theory, we hypothesized that providing information of CSR practices will affect the organizational attractiveness for prospective applicants. Participants (N=333) viewed job postings from four companies and rated the company attractiveness. Findings demonstrated that providing information of CSR practices positively affects the organizational attractiveness. In general, this research contributes to CSR and Communication literature by showing the importance of providing information of CSR for prospective applicants in the job postings. Findings empirically show that providing CSR information will affect company attractiveness in the job choice among prospective applicants. At a practical level, the findings strengthen the importance of providing information of CSR practices during the recruitment. Companies can use their engagement in CSR to raise their attractiveness among prospective applicants.